Lumbar Spondylosis: Occurrence by Gender and Age Strata at a Central Hospital, Ughelli in Nigeria - Ese, Anibar; Ahama, Efe; Oghenekohwo, Owarieta Edith (Journal of College of Medical Sciences-Nepal, 2022)
Introduction Lumbar spondylosis (LS) is an abnormal growth of vertebral bones which is prevalent among individual and causes aging and trauma. The aim of the study is to determine the prevalence of LS at the Central Hospital, Ughelli. Methods A purposive sampling technique was utilized and data was subjected to SPSS version 25. The study adopted a retrospective and descriptive study design, which involved 261 females and 113 males. Totality of 374 lateral radiographs of patients aged 18years and above were utilized. Results LS was widespread among the subjects (n=298, 79.7%). It is found to be more prevalent among age group of 65-74 years, there was no significant association between age and occurrence of LS (x2 = 5.329; df = 1; n = 374; P = 0.255). In females LS was more prevalent among subjects in age group of 45-65 years while subjects >74 years had the least prevalence. There was no significant age variation in the prevalence of LS among females (x2 = 4.553; df = 4; n = 261; P = 0.336). In males LS was more prevalent among subjects in age group of 65-74 years while subjects in age group 35-44 years had the least prevalence. There was a significant age variation in the prevalence of LS among males (x2 = 13.559; df = 4; n = 113; P = 0.009). Conclusions This study showed high occurrence of LS. Its pervasiveness is peaked at age 65-74 years and 45-54 years in males and females respectively.